Basis Pemajakan Konsumsi dan Penghasilan: Perspektif Pemerintah dan Wajib Pajak - Gultom, Yulifar Amin (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
In taxation, there are two frequently used tax based, income and consumption. According to Indonesia’s tax ratio data, Indonesiaia is still heavily relying to tax income in the form of value added taxes (consumption-based). This study attempts to see which tax base is better in taxpayer’s and government’s perspective. Consumption-based taxation is limited to value added taxes and consumption is limited to household consumption. Meanwhile, income-based taxation is limited to personal income taxes and income is limited to household income. Methods used in this study is mixed method, by doing descriptive study and grounded theory. Discussion is based on the function of taxes, which is budgetair, regulerend, stability, and income redistribution. This study shows that consumption-based taxation is better for government and income-based taxation is better for taxpayer. But, with the rise on income-based taxation, the government will be able to gain additional benefit in the future. Therefore, the government must pay more attention to income-based taxation.